Religious Beliefs, Gender Consciousness, and Women's Political Participation. - Cassese, Erin; Holman, Mirya (Sex Roles, 2016)
Organized religion affords the faithful a variety of civic skills that encourage political participation. Women are more religious than are men by most measures, but religious women do not participate in politics at elevated rates. This discrepancy suggests a puzzle: religion may have a different effect on the political mobilization of men and women. In the present paper, we explore the effect of biblical literalism-a widespread belief that the Bible is the actual word of God, to be taken literally-on political participation. Using the 2012 American National Election Study, we find support for our two hypotheses: (a) biblical literalism is associated with lower levels of gender consciousness, as measured by perceptions of discrimination and strength of ties to women as a group, and (b) reductions in these two factors account for lower political participation among women. Our findings provide new insights into the ways religious and gender identities intersect to influence political mobilization among women, with interesting implications for an American political climate where gender and religion both represent fundamental identities that shape political behavior.